The organization of informal pathways into STEM: designing towards equity. Issue 5 (24th March 2021) - Hinojosa, Leighanna; Swisher, Esmarie; Garneau, Nicole
ABSTRACT: The goal of inclusive design to promote participation of marginalised groups in science is ubiquitous across informal science education, and in the growing field of citizen science. Yet the aspiration of equality in the sciences continues to be met with challenges. Despite decades of educational research studying the barriers of participation in science, progress has not yet reached expectation. In this paper we apply an ethnographic approach to examine outcomes of a diversification effort of a citizen science programme in a museum-based genetics lab. We analyse data from interviews, artifacts and observations with participants from the programme inside the lab. We share findings about how being intentional while designing towards equity resulted in a more diverse and accessible programme while giving the participants the opportunity to build knowledge of, and skills in, genetics in an inclusive space. This paper concludes with findings on barriers to participation among individuals from underrepresented communities, and how relationships with diverse leaders can facilitate boundary crossings, foster positive identities in sciences and beget a new generation of diverse scientists.